Símbolos sacrificiais: o cordeiro e o pastor na narrativa Joanina - Oliveira, Carlos Luiz de Sousa (2023)
Based on the mimetic theory of René Girard, this research approached the sacrificial symbols of the Gospel of John, in the episodes of the testimony of John the Baptist, the Wedding at Cana and the Purification of the Temple, with emphasis on the symbology of the lamb and the shepherd associated with Jesus by the author of the Gospel of John. We have analyzed the structuring of the characterization of Jesus as both lamb and shepherd, that is, as sacrificial being and as priest who leads the sacrificial process, using symbols enshrined in Hebrew Scripture to constitute an anti-sacrificial narrative. To understand this literary enterprise, we present the central concepts of René Girard's thought: the mimetic origin of desire, the mechanism of the scapegoat, and the Bible as a critical reading of sacrificial practices. The critique of sacrificial processes is fully realized by Passion by revealing the innocence of Jesus, a new paradigm is instituted that also reveals the innocence of all previous sacrificial victims. Therefore, Christianity strikes at the structure that maintains archaic societies and makes its own survival impossible. What was found in our study was the use of the vast symbolic-literary resources of the Hebrew Scripture, in John's Gospel, to sustain the innocence of Jesus, killed to placate a social crisis, as well as to proclaim that all sacrificial victims, since the beginning of the humanization process, have always been innocent.